Antiarrhythmic Drug Therapy for Rhythm Control in Atrial Fibrillation. (January 2017) - Waks, Jonathan W.; Zimetbaum, Peter
Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and affects over 33 million people worldwide. AF is associated with stroke and systemic thromboembolism, unpleasant symptoms and reduced quality of life, heart failure, and increased mortality, and treatment of AF and its complications are associated with significant cost. Antiarrhythmic drugs (AADs) can suppress AF, allowing long-term maintenance of sinus rhythm, and have the potential to relieve symptoms and reverse or prevent adverse effects associated with AF. However, large randomized controlled studies evaluating use of AADs have not demonstrated a clear benefit to maintaining sinus rhythm, and AADs often have significant limitations, including a modest rate of overall success at maintaining sinus rhythm, frequent side effects, and potentially life-threatening toxicities. Although some of the currently available AADs have been available for almost 100 years, better tolerated and more efficacious AADs have recently been developed both for long-term maintenance of sinus rhythm and for chemical cardioversion of AF to sinus rhythm. Advances in automated AF detection with cardiac implantable electronic devices have suggested that AADs might be useful for suppressing AF to allow safe discontinuation of anticoagulation in select patients who are in sinus rhythm for prolonged periods of time. AADs may also have synergistic effects with catheter ablation of AF. This review summarizes the pharmacology and clinical use of currently available AADs for treatment of AF and discusses novel AADs and future directions for rhythm control in AF.